Semi-aquatic Epilamprinae cockroaches (Blattodea: Blaberidae) in Cameroon: towards a revision of continental African species of Rhabdoblatta Kirby, 1903 and Africalolampra Roth, 1995 - Nyame Mbia, Donald-L’or; Biram à Ngon, Eric Belmond; Legendre, Frédéric; Foto Menbohan, Samuel (European Journal of Taxonomy, 2024)
Although semi-aquatic cockroaches have been known for a long time, these insects remain little studied and their diversity underestimated. While a few species are known from Asia or South America, only a single one is known to be associated with water in Africa. Here, we report two species of semi-aquatic cockroaches of the subfamily Epilamprinae from Cameroon. One of these species is new: Rhabdoblatta fotoi Nyame Mbia, Legendre & Biram à Ngon sp. nov. Africalolampra camerunensis (Borg, 1902) comb. nov. was also found associated to these streams and we provide an extended description of this species, as well as for Africalolampra stipata comb. nov., also known from streams in West Africa. Another species was found in Cameroonian streams and is described here, although only identified at the family level (Blattellidae). The descriptions are based on morpho-anatomic characters, including male genitalia. Because nymphs were found primarily associated with water – more than adults – we provide a description of nymphs whenever possible. We provide molecular data (12S rRNA marker) for two of these water-associated species that we compared with published and unpublished sequences of Epilamprinae in a Maximum Likelihood approach. We also illustrate all but one species from continental Africa in the genera Africalolampra and Rhabdoblatta, including R. punctipennis (Saussure, 1895) which we reinstate. We provide a map and list of localities for Africalolampra and Rhabdoblatta spp. from continental Africa and Madagascar, as well as an identification key for species of Africalolampra. We finally discuss putative adaptations of semi-aquatic cockroaches.